1999
DOI: 10.1016/s0969-2126(99)80010-0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the first dissimilatory nitrate reductase at 1.9 Å solved by MAD methods

Abstract: The polypeptide fold of NAP and the arrangement of the cofactors is related to that of Escherichia coli formate dehydrogenase (FDH) and distantly resembles dimethylsulphoxide reductase. The close structural homology of NAP and FDH shows how small changes in the vicinity of the molybdenum catalytic site are sufficient for the substrate specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
344
2
1

Year Published

2004
2004
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 310 publications
(357 citation statements)
references
References 68 publications
10
344
2
1
Order By: Relevance
“…Therefore, our current interpretation for the nitrate species is a distorted sixcoordinated site, in which the Mo(V) ion coordinates the four sulfurs of the two pterin cofactors, S c -Cys 140 and one sixth ligand, presumably an oxo group (Scheme 1b). This is in contradiction with the structural data taken for the oxidized forms of Dd NapA [20] and other closely related enzymes [24], which indicated a hydroxyl/ water ligand in the position of the oxo group (Scheme 1a). Additional work is necessary to resolve this discrepancy.…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…Therefore, our current interpretation for the nitrate species is a distorted sixcoordinated site, in which the Mo(V) ion coordinates the four sulfurs of the two pterin cofactors, S c -Cys 140 and one sixth ligand, presumably an oxo group (Scheme 1b). This is in contradiction with the structural data taken for the oxidized forms of Dd NapA [20] and other closely related enzymes [24], which indicated a hydroxyl/ water ligand in the position of the oxo group (Scheme 1a). Additional work is necessary to resolve this discrepancy.…”
Section: Discussioncontrasting
confidence: 87%
“…The rhombic character of this signal excludes Mo(V) ion sites having coordination symmetries such as square pyramidal. On the other hand, on the basis of electron-nuclear double resonance studies of Pp NapAB [30] and the crystal structure of as-prepared Dd NapA [20], it was suggested that the nonsolvent exchangeable hyperfine couplings of the high g (resting) and azide signals in Pp NapAB originate from the protons of the b-methylene carbon of the cysteine coordinated to the oxidized Mo site. Since Dd NapA and Pp NapAB show nitrate and high g EPR signals with hyperfine couplings of similar type and magnitude (Table 1), Cys 140 should be coordinated to this Mo(V) redox state in Dd NapA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations